2012
DOI: 10.1371/journal.pone.0049727
|View full text |Cite
|
Sign up to set email alerts
|

Body Structures and Physical Complaints in Upper Limb Reduction Deficiency: A 24-Year Follow-Up Study

Abstract: ObjectiveTo describe upper body structures associated with upper limb reduction deficiency and the development of these structures over time, to examine the presence of physical complaints in this population, and to compare body structures and complaints between groups based on prosthesis use.DesignProspective cohort study with a follow-up period of 24 years, with matched able-bodied controls.SubjectsTwenty-eight patients with unilateral below-elbow reduction deficiency fitted with myoelectric prostheses, aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A longitudinal study of four children with upper-limb reductions found that three children presented minor neurological dysfunction and two children presented a complex form associated with developmental coordination disorder [ 11 ]. These findings are partially supported by another study that found that after a 24-year follow-up, individuals with unilateral upper-limb reductions report difficulties performing unilateral and bimanual motor tasks resulting in lower performance in sports and musical activities indicating a minor motor delay [ 28 ]. Changes in coactivation can provide information related to the motor control strategies of the central and peripheral nervous system [ 2 , 9 , 29 ], which can be used to improve prosthetic rehabilitation outcomes [ 11 ].…”
Section: Discussionmentioning
confidence: 60%
“…A longitudinal study of four children with upper-limb reductions found that three children presented minor neurological dysfunction and two children presented a complex form associated with developmental coordination disorder [ 11 ]. These findings are partially supported by another study that found that after a 24-year follow-up, individuals with unilateral upper-limb reductions report difficulties performing unilateral and bimanual motor tasks resulting in lower performance in sports and musical activities indicating a minor motor delay [ 28 ]. Changes in coactivation can provide information related to the motor control strategies of the central and peripheral nervous system [ 2 , 9 , 29 ], which can be used to improve prosthetic rehabilitation outcomes [ 11 ].…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, the targets can be correctly reached but with the help of compensatory movements (such as trunk flexion or rotation) that have to be avoided. Musculoskeletal pain and overuse injuries are actually a well-known problem for the upper-limb amputee population (Kontson et al, 2017 ; Postema, 2017 ). Error value of only concentrates on functional performance and does not take this point into account.…”
Section: Methodsmentioning
confidence: 99%
“…Upper limb amputees experience well-documented and self-reported disability, loss of function, and over-use injury with the loss of the upper extremity [1,2]. With this loss, individuals are faced with adapting and relearning aspects of motor control with the reduced or less easily controlled degrees of freedom (DOFs) of a prosthetic device.…”
Section: Introductionmentioning
confidence: 99%
“…In the transradial and transhumeral amputee, compensation favors the use of trunk and shoulder movements as opposed to distal prosthesis movements. While compensatory movements can be considered adaptive and help return function, there is concern that they may be connected to the prevalence of overuse injuries and structural changes observed in the spines of upper limb amputees [1,2]. Therefore, it is important to understand not only traditional motor learning in terms of accuracy, quickness, smoothness, and efficiency but also how compensatory movement and relative joint contributions in the upper limb prosthesis user change with prosthesis training.…”
Section: Introductionmentioning
confidence: 99%